Non-debt tax shield as a moderator in capital structure: evidence from Indonesia - Santiana; Pambudi, Januar Eky; Febrianto, Hendra Galuh (Jurnal Akademi Akuntansi, 2026)
Purpose: Research examines impact of growth potential, liquidity, also business risk on capital structure, with non-debt tax shield (NDTS) acting as  moderating factor in businesses listed on Indonesia Stock Exchange (IDX). Methodology/approach: Reserach uses quantitative approach with secondary data from financial statements of firms in technology industry are registered on IDX. Analysis technique employs panel data regression also Moderated Regression Analysis (MRA), using purposive sampling. Findings: The results show that business risk and growth opportunity don’t affect capital structure, while liquidity has positive effect on capital structure. Additionally, NDTS moderates the impacts of growth potential and liquidity rather than the impact of business risk on capital structure. Practical and Theoritical contribution/Originality: Research enriches the capital structure literature by extending NDTS as a moderating variable. Practically, it provides insights for technology companies in optimizing financing decisions based on business risk, growth opportunity, liquidity.on business risk, growth opportunitiy, and liquidity. Research Limitation: This study has limitations related to limited literature on NDTS, measurement constraints that may not fully reflect actual conditions, and given a somewhat short observation time and sample size, which restrict generalizability.